Slovenski jezik v dvojezičnih osnovnih šolah v Porabju danes - Munda Hirnök, Katalin (Jezik in slovstvo, 2023)
A key role in the preservation of Slovene in the Raba Region is played by the minority educational system. Based on a survey conducted among teachers of Slovene and other subjects taught bilingually in the two bilingual schools of the Raba Region (the Jožef Košič Bilingual Primary School in Gornji Senik and the Bilingual Primary School in Števanovci), the paper presents how the respondents evalu-ate their knowledge and use of languages in family and public life, the status of the Slovene language in primary schools, and various factors that support Slovene language teaching. In addition, the results show the respondents’ opinions on the Slovene language and their experiences with remote learning during the first wave of COVID-19
Keywords: manjšinski jezik; Porabje; pouk; slovenska manjšina; slovenščina; učitelji